Diagnostic delay in cystic fibrosis: lessons from newborn screening. - Wilcken, B (1983)
Newborn screening for cystic fibrosis (CF) by dried blood spot immunoreactive trypsin (IRT) assay is now feasible, but the benefits are disputed. We have studied the symptoms and signs at diagnosis in 48 babies detected during a newborn screening programme, and also the delay between presentation with symptoms and diagnosis in all 33 babies diagnosed at our CF clinic in the two years before screening began. Eleven of the 48 screened babies had meconium ileus, 16 had gastrointestinal symptoms only, and 14 had both respiratory and gastrointestinal symptoms at the time of diagnosis. Five of the remaining 7 babies developed clear cut symptoms or signs soon after diagnosis. Thus, 96% (46 of 48) of the babies had symptoms by 3 months of age. Of the 33 infants diagnosed clinically in the two years immediately before screening, 13 (39%) were over 12 months of age at diagnosis. Moreover, the mean delay between presentation with symptoms and diagnosis of CF in these infants was 2.6 years. Our data show that the delay between onset of symptoms and diagnosis is far greater than previously supposed and that most babies detected by our screening programme already had symptoms that warranted treatment at the time of their diagnosis.